การประเมินมูลค่าตราสารสิทธิสลับผลประโยชน์การเสียชีวิตสำหรับกรมธรรม์ประกันชีวิตยูนิเวอร์แซลไลฟ์แบบเพิ่มขึ้นภายใต้ประสบการณ์การตายของไทย - ทรงพล ภาวะรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The purpose of this research is to assess the death benefit switch option value by quantifying the actuarial present value of the option under stochastic interest rates as Cox-Ingersoll-Ross (CIR). The valuation is considered to two premium payment options after switching, which are level and risk premium payment scenarios. The mortality rates used in this study are the Thai Mortality Ordinary of 2008 (TMO2008), the mortality rates of the adjusted insured lives with mortality improvement scales and the mortality rates of Thai population from Gompertz-Gamma Frailty model. The data sets consist of government bonds prices from Thai Bond Market Association (ThaiBMA) during January 2, 2008 to December 28, 2012, the number of population and the number of death classified by age and sex during year 2008 to year 2012 from the Ministry of Interior and the Ministry of Public Health, respectively. The findings are found that the more policyholder survives after switching, the more option value gets increase and the switch probabilities made the highest option value are approximately 2.5% - 5% and 0.5% - 2.5% for level and risk premium payment scenarios, respectively. The option value for the policyholder who has good health status or low frailty level is higher than for the one who has bad health status or high frailty level and the option value assessed from TMO2008 is higher than assessed from the mortality rates of the adjusted insured lives with mortality improvement scales.